Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams After a few more weeks the Insurance Officer called Adam up on one of his signing days and told him he would have to seek some other line of work or risk being disallowed benefit on the ground of not being really available for employment. Would he like a course of training for light engineering at a Government Training Centre? Probably he would have to be "directed" by the Ministry of Labour to some other town for the sixteen weeks of training and for suitable work afterwards. They could not let him continue drawing unemployment money and going to seed while waiting for a light job of a special kind which scarcely existed in the area. However, his travel and removal expenses were to be paid ; also temporary lodgings found. Adam hated changing his trade and did not relish moving his home ; but what was the alternative? Benefit would stop. He had a bit of money saved, but not enough to live on. He was a young man. If he applied to the National Assistance office the means test would not be too severe, but it hurt his pride to think of himself sinking into the class of dilapidated human beings who had to seek relief. He accepted the training and went. Adam knew that thousands of ex-Service men were in a like case ; they had to change their line of work to fit in with the changing incidence of labour demand. More fluidity in the labour market was the order of the day ; it was the only way to keep up a high level of employment. ADAM BLACK MARRIES EVE BROWN Adam went to a Government Training Centre in the Bristol area. His course was in light engineering, precision work which required a good deal of learning ; but he was an intelligent man, fitted for something better than his old work. The Ministry of Labour paid him a 42 15X/2/566/303